Correlation of PCSK1 with nonalcoholic fatty liver disease in a Han Chinese population: a case-control observational study. Issue 3 (8th September 2022) - Yang, Xiao; Yuan, Fan; Wu, Na; Ren, Decheng; Liu, Liangjie; Bi, Yan; Ji, Lei; Han, Ke; Feng, Mofan; Su, Kai; Yang, Fengping; Wu, Xi; et al.
Abstract : Objective: This study aimed to investigate the association between single-nucleotide polymorphisms (SNPs) of PCSK1 (proprotein convertase subtilisin/kexin type 1) related to obesity and nonalcoholic fatty liver disease (NAFLD). Methods: In this case-control observational study, four candidate SNPs (rs6234, rs155971, rs6232, rs3811951) of PCSK1 were genotyped in 732 NAFLD patients and 823 healthy control participants, all of whom were of ethnic Han Chinese descent. All participants came from Shanghai, China, and joined our study during 2015 to 2016. The frequencies of each allele and genotype, paired linkage disequilibrium, and haplotype were calculated on the SHEsis platform. In addition to SHEsis, five different genetic models (codominant, dominant, recessive, overdominant, and log-additive) were employed to identify the correlation between genotype frequency and NAFLD. This study was approved by the Medical Ethics Committee of Shanghai University of Traditional Chinese Medicine on December 18, 2017 (approved No. 2017LCSY069). Results: In a comparison of NAFLD patients and healthy participants, none of the four PCSK1 SNPs were significantly correlated with the occurrence of NAFLD ( P > 0.05), in either genotypic or allelic distribution. The recessive model of rs3811951 appeared to show a correlation (odds ratio = 1.077; 95% confidence interval = 0.924–1.256; P = 0.04), but there was no statistical significance after Bonferroni correction ( P corr > 0.0125). Conclusions: Four obesity-related PCSK1 SNPs (rs6234, rs155971, rs6232, rs3811951) showed no significant correlation with the development of NAFLD in a Han Chinese population.